2017
DOI: 10.1080/0284186x.2017.1343494
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI of the microenvironment of pancreatic adenocarcinoma xenografts

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease with poor outcome. Resistance to treatment is associated with impaired vascularity, extensive hypoxia, and interstitial hypertension. In this study, the potential of dynamic contrast-enhanced (DCE)-MRI as a method for assessing the microvascular density (MVD), the fraction of hypoxic tissue, and the interstitial fluid pressure (IFP) of PDACs was investigated. Material and methods: Intramuscular BxPC-3, Capan-2, MIAPaCa-2, and Panc-1 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 51 publications
(77 reference statements)
5
29
1
Order By: Relevance
“…Figure contains a bar graph showing the mean and SD measurements of v p , K trans , v e , and K ep from the control, tumor, and nontumoral regions. The results for all categories were in general agreement with published values from literature . An analysis of variance analysis with Holm‐Bonferroni correction indicated that all 4 parameters were significantly different between tumor with non‐tumor ( P = .002, .003, <.001, and .004, respectively) and between tumor and control ( P = .0011, <.001, <.001, and <.001, respectively).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Figure contains a bar graph showing the mean and SD measurements of v p , K trans , v e , and K ep from the control, tumor, and nontumoral regions. The results for all categories were in general agreement with published values from literature . An analysis of variance analysis with Holm‐Bonferroni correction indicated that all 4 parameters were significantly different between tumor with non‐tumor ( P = .002, .003, <.001, and .004, respectively) and between tumor and control ( P = .0011, <.001, <.001, and <.001, respectively).…”
Section: Resultssupporting
confidence: 89%
“…The estimates of the kinetic parameters v p , K trans , v e , and K ep of control and patient groups are generally in line with the values published in the literature . K trans and v e have been shown to correlate with the microvascular density and fibrosis in PDAC lesions, respectively, and therefore can be used as imaging markers of the perfusion properties of tumor . In the TK model, K trans is dominated by the tissue blood flow and the capillary permeability–surface area and can have different physiological interpretations depending on the balance between the 2 factors .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Interstitial pressure is higher in the TME than in nonmalignant tissue 218–221 . This difference can affect drug diffusion and delivery, as demonstrated in PDAC 222,223 , melanoma 224 or glioma 225 .…”
Section: Effects Of Tumour Stroma On Therapymentioning
confidence: 99%